Video Profil Pemandian Sapta Tirta Pablengan Matesih Kabupaten Karanganyar - ., Kusmiyati; Nugroho, Gesang Kristianto (APMMI - Asosiasi Profesi Multimedia Indonesia, 2009)
Multimedia is one represent of way correct to water down to submit the information in the form of visual audio or visual. The multimedia also can be result the something more live and draw, of one applying multimedia is to visualizing the profile video. The Bath Water Sapta Tirta pablengan not yet owned the medium to promote to society. By using profile video expected to earn as a means of promotion to society at the same time as documentation.The abbreviation of problem from this research is how to make the profile The Bath Water Warm of Bayanan by using multimedia computer. As for intention of this research is to make the profile video and information media The Bath Water Warm of Bayanan. The benefit from the research can use is as a promotion media and documentation of The Bath Water Sapta Tirta pablengan. The reseach methodologies used by book, observation, the interview, analysis, scheme, in take draw and capturing, editing and voice recording, test-drive and implementation.Conclusin from making of profile video by using this computer multimedia the purpose of the documentation of the same time as promotion medium.